Conference Report: Issues Affecting Rural Communities, July 10-15, 1994, Townsville, Australia - Theodore Coladarci (Journal of Research in Rural Education, 1995)
The following is a report of the July 1994 international conference, Issues Affecting Rural Communities, which was held in Townsville, Australia, and hosted by the Rural Education Research and Development Centre (of James Cook University of North Queensland). This report comprises an introduction by David McSwan, a review of central issues by Ted Scott, a summary of emerging themes by Toni Haas, and a culminating Statement of Principle and resolutions. Conference proceedings are available by writing to the Rural Education Research and Development Centre.